Wavelength, concentration, and distance dependence of nonradiative energy transfer to a plane of gold nanoparticles. - Bradley, Louise; Gounko, Iouri (My University, 2012)
Nonradiative energy transfer to metal nanoparticles is a technique used for optical-based distance measurements which is often implemented in sensing. Both Förster resonant energy transfer (FRET) and nanometal surface energy transfer (NSET) mechanisms have been proposed for emission quenching in proximity to metal nanoparticles. Here quenching of emission of colloidal quantum dots in proximity to a monolayer of gold nanoparticles is investigated. Five differently sized CdTe quantum dots are used to probe the wavelength dependence of the quenching mechanism as their emission peak moves from on resonance to off resonance with respect to the localized surface plasmon peak of the gold nanoparticle layer. The gold nanoparticle concentration and distance dependences of energy transfer are discussed. Photoluminescence quenching and lifetime data are analyzed using both FRET and NSET models and the extracted characteristic distances are compared with theory. Good agreement with FRET theory has been found for quantum dots with emission close to the localized surface plasmon resonance, though larger than expected Förster radii are observed for quantum dots with emission red-shifted with respect to the localized surface plasmon peak. Closer agreement between experimental and theoretical characteristic distances can be found across the full wavelength range within a NSET approach.
PUBLISHED
Keywords: surface plasmons